Maternal Prolactin Inhibition Causes Changes in Leptin at 22- and 30-Day-Old Pups - Carvalho, J. C.; de Oliveira, E.; Peixoto-Silva, N.; Fraga, M. C.; Nobre, J. L.; Lisboa, P. C.; Moura, E. G. (Hormone and Metabolic Research, 2015)
Breastfeeding is associated with obesity prevention. We showed previously that prolactin inhibition at the end of lactation causes hyperleptinemia at weaning (PN21) and programs for obesity, insulin resistance, dyslipidemia, and leptin resistance (PN180). Here, we evaluate the source of neonatal hyperleptinemia and how it develops during the nutritional transition from milk through solid food. Lactating rats were treated with bromocriptine (BRO), a prolactin inhibitor, 0.5 mg twice a day, or saline (CON) for the last 3 days of lactation. All parameters were studied at PN22 and PN30. At PN22, BRO-treated rats showed lower food intake, body mass, and body length. At PN30, only body length and mesenteric fat mass were lower. Despite normal plasma leptin levels at PN22, the adipose tissue leptin mRNA expression was lower, while plasma leptin was higher in PN30, possibly due to a higher adipose mesenteric tissue production. At PN22, the hypothalamus seems to be more sensitive to leptin, since OBR and STAT3 are higher. Conversely, at PN30 leptin signaling pathway is suggestive of leptin resistance with lower STAT3 and higher SOCS3 in hypothalamus and consequently higher NPY. Glycemia was lower at PN22 and higher at PN30, without changes in plasma insulin levels. At PN30, BRO-treated rats had other metabolic changes such as higher plasma cholesterol, lower HDL-c, higher hepatic cholesterol and AST, suggesting a liver dysfunction. Our data show that milk supply can exert a crucial role in the imprinting of a second leptin peak, which is important for survival adaptation to adverse nutritional conditions.
Keywords: early weaning; bromocriptine; hyperleptinemia; leptin resistance